Developmental universities in inclusive innovation systems : alternatives for knowledge democratization in the global South /: alternatives for knowledge democratization in the global South. ([2018]) - Arocena, Rodrigo; Göransson, Bo, 1953-; Sutz, Judith
No abstract available